The Deubiquitinase OTUD1 Influences HIV-1 Release by Regulating the Host Restriction Factor BST-2 - Man-Di Zhang; Fan Chen; Wen-Qiang He; Ying Lu; Feng-Liang Liu; Hong-Guang Zhang; Liu-Meng Yang; Chun-Sheng Dong; Si-Dong Xiong; Yong-Tang Zheng (Viruses)
Bone marrow stromal cell antigen 2 (BST-2) is a restriction factor for human immunodeficiency virus type I (HIV-1) and plays an important role in regulating the release of viral particles. However, the antiviral efficacy of BST-2 is antagonized by the HIV-1-encoded accessory protein Vpu, which facilitates the degradation of BST-2 by recruiting E3 ubiquitin ligase β-TrCP. The involvement of deubiquitinases (DUBs) in counteracting BST-2 ubiquitination and influencing its stability during HIV-1 infection remains inadequately explored. In this study, we conducted a small interfering RNA (siRNA) screening of human DUBs and determined that OTUD1 interacts with BST-2, leading to a reduction in its K48- and K63-linked ubiquitination. This reduction increases BST-2 protein stability, and subsequently inhibits HIV-1 release. Our findings reveal a novel regulatory mechanism by which DUBs influence the stability of the HIV-1 restriction factor BST-2 to dampen viral release, providing a potential therapeutic target for HIV-1 antiviral intervention.